Safe Haskell | Safe-Infered |
---|
- all2s :: (Enum a, Enum b, Eq a, Eq b, Bounded a, Bounded b) => [(a, b)]
- all3s :: (Enum a, Enum b, Enum c, Eq a, Eq b, Eq c, Bounded a, Bounded b, Bounded c) => [(a, b, c)]
- all4s :: (Enum a, Enum b, Enum c, Enum d, Eq a, Eq b, Eq c, Eq d, Bounded a, Bounded b, Bounded c, Bounded d) => [(a, b, c, d)]
- all5s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Eq a, Eq b, Eq c, Eq d, Eq e, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e) => [(a, b, c, d, e)]
- all6s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f) => [(a, b, c, d, e, f)]
- all7s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g) => [(a, b, c, d, e, f, g)]
- all8s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h) => [(a, b, c, d, e, f, g, h)]
- all9s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i) => [(a, b, c, d, e, f, g, h, i)]
- all10s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j) => [(a, b, c, d, e, f, g, h, i, j)]
- all11s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k) => [(a, b, c, d, e, f, g, h, i, j, k)]
- all12s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l) => [(a, b, c, d, e, f, g, h, i, j, k, l)]
- all13s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Enum m, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Eq m, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l, Bounded m) => [(a, b, c, d, e, f, g, h, i, j, k, l, m)]
- all14s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Enum m, Enum n, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Eq m, Eq n, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l, Bounded m, Bounded n) => [(a, b, c, d, e, f, g, h, i, j, k, l, m, n)]
- all15s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Enum m, Enum n, Enum o, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Eq m, Eq n, Eq o, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l, Bounded m, Bounded n, Bounded o) => [(a, b, c, d, e, f, g, h, i, j, k, l, m, n, o)]
- hyperplaneSize :: Int -> Int -> Int
- fe :: [Int] -> Int
- te :: Int -> Int -> [Int]
- to2Tuple :: (J t, J t1) -> (t, t1)
- to3Tuple :: ((J t, J t1), J t2) -> (t, t1, t2)
- to4Tuple :: (((J t, J t1), J t2), J t3) -> (t, t1, t2, t3)
- to5Tuple :: ((((J t, J t1), J t2), J t3), J t4) -> (t, t1, t2, t3, t4)
- to6Tuple :: (((((J t, J t1), J t2), J t3), J t4), J t5) -> (t, t1, t2, t3, t4, t5)
- to7Tuple :: ((((((J t, J t1), J t2), J t3), J t4), J t5), J t6) -> (t, t1, t2, t3, t4, t5, t6)
- to8Tuple :: (((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7) -> (t, t1, t2, t3, t4, t5, t6, t7)
- to9Tuple :: ((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8) -> (t, t1, t2, t3, t4, t5, t6, t7, t8)
- to10Tuple :: (((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9)
- to11Tuple :: ((((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9), J t10) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9, t10)
- to12Tuple :: (((((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9), J t10), J t11) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9, t10, t11)
- to13Tuple :: ((((((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9), J t10), J t11), J t12) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9, t10, t11, t12)
- to14Tuple :: (((((((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9), J t10), J t11), J t12), J t13) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9, t10, t11, t12, t13)
- to15Tuple :: ((((((((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9), J t10), J t11), J t12), J t13), J t14) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9, t10, t11, t12, t13, t14)
- from2Tuple :: (a, a1) -> (J a, J a1)
- from3Tuple :: (a, a1, a2) -> ((J a, J a1), J a2)
- from4Tuple :: (a, a1, a2, a3) -> (((J a, J a1), J a2), J a3)
- from5Tuple :: (a, a1, a2, a3, a4) -> ((((J a, J a1), J a2), J a3), J a4)
- from6Tuple :: (a, a1, a2, a3, a4, a5) -> (((((J a, J a1), J a2), J a3), J a4), J a5)
- from7Tuple :: (a, a1, a2, a3, a4, a5, a6) -> ((((((J a, J a1), J a2), J a3), J a4), J a5), J a6)
- from8Tuple :: (a, a1, a2, a3, a4, a5, a6, a7) -> (((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7)
- from9Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8) -> ((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8)
- from10Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9) -> (((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9)
- from11Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9, a10) -> ((((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9), J a10)
- from12Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11) -> (((((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9), J a10), J a11)
- from13Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11, a12) -> ((((((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9), J a10), J a11), J a12)
- from14Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11, a12, a13) -> (((((((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9), J a10), J a11), J a12), J a13)
- from15Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11, a12, a13, a14) -> ((((((((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9), J a10), J a11), J a12), J a13), J a14)
- class Enum a where
- succ :: a -> a
- pred :: a -> a
- toEnum :: Int -> a
- fromEnum :: a -> Int
- enumFrom :: a -> [a]
- enumFromThen :: a -> a -> [a]
- enumFromTo :: a -> a -> [a]
- enumFromThenTo :: a -> a -> a -> [a]
Documentation
all2s :: (Enum a, Enum b, Eq a, Eq b, Bounded a, Bounded b) => [(a, b)]Source
generate all 2-tuples (of enumerable values) so that the sum of the 2 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all3s :: (Enum a, Enum b, Enum c, Eq a, Eq b, Eq c, Bounded a, Bounded b, Bounded c) => [(a, b, c)]Source
generate all 3-tuples (of enumerable values) so that the sum of the 3 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all4s :: (Enum a, Enum b, Enum c, Enum d, Eq a, Eq b, Eq c, Eq d, Bounded a, Bounded b, Bounded c, Bounded d) => [(a, b, c, d)]Source
generate all 4-tuples (of enumerable values) so that the sum of the 4 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all5s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Eq a, Eq b, Eq c, Eq d, Eq e, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e) => [(a, b, c, d, e)]Source
generate all 5-tuples (of enumerable values) so that the sum of the 5 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all6s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f) => [(a, b, c, d, e, f)]Source
generate all 6-tuples (of enumerable values) so that the sum of the 6 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all7s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g) => [(a, b, c, d, e, f, g)]Source
generate all 7-tuples (of enumerable values) so that the sum of the 7 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all8s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h) => [(a, b, c, d, e, f, g, h)]Source
generate all 8-tuples (of enumerable values) so that the sum of the 8 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all9s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i) => [(a, b, c, d, e, f, g, h, i)]Source
generate all 9-tuples (of enumerable values) so that the sum of the 9 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all10s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j) => [(a, b, c, d, e, f, g, h, i, j)]Source
generate all 10-tuples (of enumerable values) so that the sum of the 10 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all11s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k) => [(a, b, c, d, e, f, g, h, i, j, k)]Source
generate all 11-tuples (of enumerable values) so that the sum of the 11 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all12s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l) => [(a, b, c, d, e, f, g, h, i, j, k, l)]Source
generate all 12-tuples (of enumerable values) so that the sum of the 12 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all13s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Enum m, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Eq m, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l, Bounded m) => [(a, b, c, d, e, f, g, h, i, j, k, l, m)]Source
generate all 13-tuples (of enumerable values) so that the sum of the 13 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all14s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Enum m, Enum n, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Eq m, Eq n, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l, Bounded m, Bounded n) => [(a, b, c, d, e, f, g, h, i, j, k, l, m, n)]Source
generate all 14-tuples (of enumerable values) so that the sum of the 14 fromEnum-values is monotonic increasing fromEnum :: a -> Int
all15s :: (Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Enum m, Enum n, Enum o, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Eq m, Eq n, Eq o, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l, Bounded m, Bounded n, Bounded o) => [(a, b, c, d, e, f, g, h, i, j, k, l, m, n, o)]Source
generate all 15-tuples (of enumerable values) so that the sum of the 15 fromEnum-values is monotonic increasing fromEnum :: a -> Int
hyperplaneSize :: Int -> Int -> IntSource
to7Tuple :: ((((((J t, J t1), J t2), J t3), J t4), J t5), J t6) -> (t, t1, t2, t3, t4, t5, t6)Source
to8Tuple :: (((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7) -> (t, t1, t2, t3, t4, t5, t6, t7)Source
to9Tuple :: ((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8) -> (t, t1, t2, t3, t4, t5, t6, t7, t8)Source
to10Tuple :: (((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9)Source
to11Tuple :: ((((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9), J t10) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9, t10)Source
to12Tuple :: (((((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9), J t10), J t11) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9, t10, t11)Source
to13Tuple :: ((((((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9), J t10), J t11), J t12) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9, t10, t11, t12)Source
to14Tuple :: (((((((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9), J t10), J t11), J t12), J t13) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9, t10, t11, t12, t13)Source
to15Tuple :: ((((((((((((((J t, J t1), J t2), J t3), J t4), J t5), J t6), J t7), J t8), J t9), J t10), J t11), J t12), J t13), J t14) -> (t, t1, t2, t3, t4, t5, t6, t7, t8, t9, t10, t11, t12, t13, t14)Source
from2Tuple :: (a, a1) -> (J a, J a1)Source
from3Tuple :: (a, a1, a2) -> ((J a, J a1), J a2)Source
from4Tuple :: (a, a1, a2, a3) -> (((J a, J a1), J a2), J a3)Source
from5Tuple :: (a, a1, a2, a3, a4) -> ((((J a, J a1), J a2), J a3), J a4)Source
from6Tuple :: (a, a1, a2, a3, a4, a5) -> (((((J a, J a1), J a2), J a3), J a4), J a5)Source
from7Tuple :: (a, a1, a2, a3, a4, a5, a6) -> ((((((J a, J a1), J a2), J a3), J a4), J a5), J a6)Source
from8Tuple :: (a, a1, a2, a3, a4, a5, a6, a7) -> (((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7)Source
from9Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8) -> ((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8)Source
from10Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9) -> (((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9)Source
from11Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9, a10) -> ((((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9), J a10)Source
from12Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11) -> (((((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9), J a10), J a11)Source
from13Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11, a12) -> ((((((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9), J a10), J a11), J a12)Source
from14Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11, a12, a13) -> (((((((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9), J a10), J a11), J a12), J a13)Source
from15Tuple :: (a, a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11, a12, a13, a14) -> ((((((((((((((J a, J a1), J a2), J a3), J a4), J a5), J a6), J a7), J a8), J a9), J a10), J a11), J a12), J a13), J a14)Source
class Enum a where
Class Enum
defines operations on sequentially ordered types.
The enumFrom
... methods are used in Haskell's translation of
arithmetic sequences.
Instances of Enum
may be derived for any enumeration type (types
whose constructors have no fields). The nullary constructors are
assumed to be numbered left-to-right by fromEnum
from 0
through n-1
.
See Chapter 10 of the Haskell Report for more details.
For any type that is an instance of class Bounded
as well as Enum
,
the following should hold:
- The calls
andsucc
maxBound
should result in a runtime error.pred
minBound
-
fromEnum
andtoEnum
should give a runtime error if the result value is not representable in the result type. For example,
is an error.toEnum
7 ::Bool
-
enumFrom
andenumFromThen
should be defined with an implicit bound, thus:
enumFrom x = enumFromTo x maxBound enumFromThen x y = enumFromThenTo x y bound where bound | fromEnum y >= fromEnum x = maxBound | otherwise = minBound
succ :: a -> a
the successor of a value. For numeric types, succ
adds 1.
pred :: a -> a
the predecessor of a value. For numeric types, pred
subtracts 1.
Convert from an Int
.
Convert to an Int
.
It is implementation-dependent what fromEnum
returns when
applied to a value that is too large to fit in an Int
.
enumFrom :: a -> [a]
Used in Haskell's translation of [n..]
.
enumFromThen :: a -> a -> [a]
Used in Haskell's translation of [n,n'..]
.
enumFromTo :: a -> a -> [a]
Used in Haskell's translation of [n..m]
.
enumFromThenTo :: a -> a -> a -> [a]
Used in Haskell's translation of [n,n'..m]
.
Enum Bool | |
Enum Char | |
Enum Double | |
Enum Float | |
Enum Int | |
Enum Integer | |
Enum Ordering | |
Enum () | |
Integral a => Enum (Ratio a) | |
(Enum a, Enum b, Eq a, Eq b, Bounded a, Bounded b) => Enum (a, b) | |
(Enum a, Enum b, Enum c, Eq a, Eq b, Eq c, Bounded a, Bounded b, Bounded c) => Enum (a, b, c) | |
(Enum a, Enum b, Enum c, Enum d, Eq a, Eq b, Eq c, Eq d, Bounded a, Bounded b, Bounded c, Bounded d) => Enum (a, b, c, d) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Eq a, Eq b, Eq c, Eq d, Eq e, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e) => Enum (a, b, c, d, e) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f) => Enum (a, b, c, d, e, f) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g) => Enum (a, b, c, d, e, f, g) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h) => Enum (a, b, c, d, e, f, g, h) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i) => Enum (a, b, c, d, e, f, g, h, i) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j) => Enum (a, b, c, d, e, f, g, h, i, j) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k) => Enum (a, b, c, d, e, f, g, h, i, j, k) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l) => Enum (a, b, c, d, e, f, g, h, i, j, k, l) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Enum m, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Eq m, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l, Bounded m) => Enum (a, b, c, d, e, f, g, h, i, j, k, l, m) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Enum m, Enum n, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Eq m, Eq n, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l, Bounded m, Bounded n) => Enum (a, b, c, d, e, f, g, h, i, j, k, l, m, n) | |
(Enum a, Enum b, Enum c, Enum d, Enum e, Enum f, Enum g, Enum h, Enum i, Enum j, Enum k, Enum l, Enum m, Enum n, Enum o, Eq a, Eq b, Eq c, Eq d, Eq e, Eq f, Eq g, Eq h, Eq i, Eq j, Eq k, Eq l, Eq m, Eq n, Eq o, Bounded a, Bounded b, Bounded c, Bounded d, Bounded e, Bounded f, Bounded g, Bounded h, Bounded i, Bounded j, Bounded k, Bounded l, Bounded m, Bounded n, Bounded o) => Enum (a, b, c, d, e, f, g, h, i, j, k, l, m, n, o) |